The Relationship Between Facial Expression and Cognitive Function in Patients With Depression - Ruihua, Ma; Hua, Guo; Meng, Zhao; Nan, Chen; Panqi, Liu; Sijia, Liu; Jing, Shi; Yunlong, Tan; Shuping, Tan; Fude, Yang; Li, Tian; Zhiren, Wang (Frontiers in Psychology, 2021)
Objective: Considerable evidence has shown that facial expression recognition ability and cognitive function are impaired in patients with depression. We aimed to investigate the relationship between facial expression recognition and cognitive function in patients with depression. Method：A total of 51 participants (31 depression patients and 20 healthy control subjects) underwent facial expression recognition tests measuring anger, fear, disgust, sadness, happiness, and surprise. The Chinese version of the MATRICS Consensus Cognitive Battery (MCCB), which assesses seven cognitive domains, was used. Result: Compared with the control group, there were differences in the recognition of the expressions of sadness (p=0.036), happiness (p=0.041), and disgust (p=0.030) in the depression group. In terms of cognitive function, the scores of patients with depression in the trail making test (p<0.001), symbol coding (p<0.001), spatial span (p<0.001), mazes (p=0.007), brief visuospatial memory test (p=0.001), category fluency (p=0.029), and continuous performance test (p=0.001) were lower than those of the control group, and the difference was statistically significant. The accuracy of sadness and disgust expression recognition in patients with depression was significantly positively correlated with cognitive function scores. Deficits in sadness expression recognition were significantly correlated with the trail making test (p=0.001, r=0.561), symbol coding (p=0.001, r=0.596), maze (p=0.015, r=0.439), and brief visuospatial memory test (p=0.044, r=0.370). Deficits in disgust expression recognition were significantly correlated with impairments in the trail-making test (p=0.005, r=0.501) and symbol coding (p=0.001, r=0.560). Conclusion: As cognitive function is impaired in patients with depression, the ability to recognize negative facial expressions declines, which is mainly reflected in processing speed, reasoning, problem-solving, and memory.